Information Processing in Cells and Tissues : 10th International Conference, IPCAT 2015, San Diego, CA, USA, September 14-16, 2015, Proceedings - Lones, Michael; Tyrrell, Andy.; Smith, Stephen; Fogel, Gary.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 10th International Conference on Information Processing in Cells and Tissues, IPCAT 2015, held in San Diego, CA, USA, in September 2015. The 19 papers presented in this volume were carefully reviewed and selected from 22 submissions. They were organized in topical sections named: biochemical information processing; collective and distributed behavior; patterning and rhythm generation; biochemical regulatory networks; metabolomics and phenotypes; and neural modelling and neural networks.
Keywords: Bioinformatics; Computer science; Optical pattern recognition; Computational Biology/Bioinformatics.; Bioinformatics; Computation by Abstract Devices; Math Applications in Computer Science; Pattern Recognition